"Orang Asing”: Berteologi Bersama Mahasiswa Migran di Kota Malang - Situmorang, Markus (Perspektif, 2006)
The social development has improved many aspect of human life, such as economic benefit, higher life style, easier mobilisation, which enables people to move from one place to another. To some extent, this migration has brought many benefits for people, however, it also creates many problems to sort out. The author notices the situation happening in the city of Malang, where many students from other places around Indonesia come to pursue higher studies. Apart from positive ideas those students bear in mind, the author highlights the fact that there is significant tension between students from different back- ground, such as races, religious beliefs, cultures, traditions, etc. Considering that this issue could raise bigger tension which could lead to broader conflict, the author proposes some theological and pastoral aproach to help these people molto come to terms with the real situation. The approach proposed is based on Biblical reference, with three key figures: Isaiah, Amos and Jesus. And finally the author suggests some concrete pastoral steps in order to promote the harmony and to bridge the gap because of the pluralism.